Fluorescence enhancement of cadmium selenide quantum dots assembled on silver nanoparticles and its application to glucose detection - Tang, Yecang (Langmuir : the ACS journal of surfaces and colloids, 2014)
In this work, a new assembled glucose sensor based on the Ag nanoparticle (AgNP)-enhanced fluorescence of CdSe quantum dots (QDs) was developed. The mercaptoglycerol-modified AgNPs and aminophenylboronic acid-functionalized CdSe QDs are assembled into AgNP-CdSe QD complexes through the formation of a boronate ester bond. As compared to that of bare CdSe QDs, up to a 9-fold fluorescence enhancement and a clear blue shift of the emission peak for AgNP-CdSe QD complexes were observed, which is attributed to the surface plasmon resonance of AgNPs. In addition, the as-formed complexes are gradually disassembled in the presence of glucose molecules because they can replace the AgNPs by competitive binding with boronic acid groups, resulting in the weakening of fluorescence enhancement. The decrease in fluorescence intensity presents a linear relationship with glucose concentration in the range from 2 to 52 mM with a detection limit of 1.86 mM. Such a metal-enhanced QDs fluorescence system may have promising applications in chemical and biological sensors